PENURUNAN KADAR FOSFAT DALAM LIMBAH CAIR RUMAH SAKIT X DENGAN MENGGUNAKAN TANAMAN AIR KAYU APU (PISTIA STRATIOTES) TAHUN 2015 - Isnia Fitri Abdillah; Suprijandani .; Fitri Rohkmalia (Poltekkes Kemenkes Surabaya, 2015)
Hospital liquid waste are all waste water including faeces derived form hospital activities.Hospitals location used to be far from settlements, now they are generally in the middle of denseresidential areas, which trigger pollution problem. Pollution problem of liquid waste often trigger conflicts between hospital and community living around it. One of the harmfull pollutant compounds is phosphate. This study aim to determine water lettuce effectiveness in reducingphosphate levels. This research was categorized as actual experimental research with “Pretest and PosttestDesign with Controlled Group”. Data was obtained from secondary and primary data. 20 liters sample was used for 3 times experiment of 15 days process. Data were than analyzed by using ANOVA test.Results shows reduction of phosphate level after treatment with water lettuce (p = 0.0000.05). LSD results showed that there was difference in phosphate level reduction on 5 days,10 days, 15 days treatment (p = 0.0000.05). Phosphate level did not exceed Threshold LimitValue (TLV) stipulated in East Java Governor Regulation No. 72 in 2013. Related institutions (hospitals with the liquid waste quality that has not meet the requirements) are suggested make pool and plants arrangement inside it. The pool is then filledwith liquid waste from outlet. Water quality of liquid waste should be improved prior to flowing it tocity.